Update on Chagas' disease in Mexico - Dumonteil Eric (Instituto Nacional de Salud Pública, 1999)
Chagas' disease, caused by the protozoan parasite Trypanosoma cruzi, represents a major public health problem in most of the American continent. As transmission of the parasite is being interrupted in most of South America, the disease remains endemic in various areas of Mexico. We review here some of the information gathered in recent years. Seroprevalence of T. cruzi infection in humans remains relatively high in some areas, and there has been a general increase in the number of chronic cases reported to health authorities in recent years. In fact, chronic chagasic cardiomyopathy appears to be affecting a large number of patients with heart disease, but many cases may be misreported because of the unspecific nature of the clinical symptoms. Epidemiological monitoring of vector and reservoir populations, as well as of human cases is helping focus on endemic areas, but a better coordination and development of these efforts is still needed. Recent studies of parasite biology are in agreement with previous work showing the great diversity of parasite characteristics, and support the need for a regional approach to this zoonosis. Strong and continuing support from health and academic authorities is thus still needed to further improve our understanding of Chagas' disease in Mexico and implement efficient control programs.